Innocent Victims and Vulnerable Offenders: Defending Impaired Adults Who Kill Children. (October 2019) - Midson, Brenda
There are few societies in which child abuse is not a serious issue, with homicide being the extreme form of such victimisation. Child homicide occurs in a wide array of circumstances but there is enough anecdotal evidence to suggest that many offenders who kill children are suffering from sometimes quite acute mental distress. There may also be other factors impacting on an offender's ability to think rationally, which may not amount to any recognised disorder. While it is imperative that we prosecute and prevent child homicide, in doing so we must avoid overlooking the realities of other vulnerable people. In rejecting a binary approach to victims and offenders, this article argues that sometimes offenders may also be vulnerable due to an impaired ability to reason or to act in a truly voluntary way. New Zealand has repealed the defence of provocation and, apart from infanticide, offers no mitigation by way of diminished responsibility. Offenders who commit child homicide, but who do not meet the legal definition of insanity, will be liable for murder even though their capacity may have been impaired or overborne by circumstances. While, in this regard, New Zealand law is particularly deficient, there is an argument that other jurisdictions also fail to adequately respond to vulnerable offenders who kill children. This article seeks to outline the failures in existing legal frameworks to assign legal responsibility for these vulnerable offenders in a way that corresponds with their moral culpability. The article will then identify and evaluate proposals for reform. As Ulbrick and others observe, in the context of arguments about defensive homicide and mentally impaired defendants, it is critical that we 'advocate for a greater range of legal responses to cover the nuance and complexities of lethal violence' (Madeleine Ulbrick, Asher Flynn and Danielle Tyson 'The Abolition of Defensive Homicide: A Step Towards Populist Punitivism at the Expense of Mentally Impaired Offenders' (2016) 40 Melb Univ Law Rev 324, 330).